Transradial Access in Interventional Radiology Background, Applications and Techniques - Fischman, Aaron M.; Patel, Rahul S.; Lookstein, Robert A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides how-to recommendations and detailed guides for using transradial access in interventional radiology. A relatively new and growing technique, transradial access is most commonly found within interventional cardiology. This book approaches those cardiac uses of transradial access while extending its use to other body sites and disease states. The book details the interventional radiologist$1 (Bs transition to using transradial access across a broad spectrum of clinical applications, allowing them to better introduce it into their practice and to their patients. The text is divided into three sections: overview, clinical applications, and novel applications and techniques. The first section covers the history of transradial access, the initial patient assessment, and how to prepare for a procedure. The second section is divided into different diseases and interventional situations where transradial access could be considered, including subclavian artery stenosis and endovascular neurosurgery. The third section includes coverage of how to perform the latest techniques and projections for future procedures. This guide provides a manual of operations to assist in the setup of the practice, from office visit to procedure room to recovery across a variety of service lines and patient populations. Key take home points and equipment summaries accompany each chapter, allowing the user to easily navigate the book to accelerate his or her practice. This is an ideal guide for interventional radiologists. .s
SECTION I: Overview -- History -- Physical Exam and Assessment -- Nursing Assessment -- Procedure Suite Set-Up -- Recovery Room Implications -- SECTION II: Clinical Applications -- Renal and Mesenteric Artery Disease -- Interventional Oncology -- Peripheral Arterial Disease (Aorto-Iliac) -- Subclavian Artery Stenosis -- Pelvic Embolization -- Hemodialysis Access Interventions -- Carotid and Vertebral Interventions -- Endovascular Neurosurgery -- Acute Hemorrhage and Trauma -- SECTION III: Novel Applications and Techniques -- Ulnar Artery Access -- Distal Radial Artery Access -- Bariatric Embolization -- Infrainguinal Endovascular Therapy.
Keywords: Radiology; Internal medicine; Radiology; Internal Medicine; Internal Medicine; Catheterization, Peripheral -- methods; Radiography, Interventional -- methods; Peripheral Nerves -- surgery; Radial Artery -- surgery